THE EFFECTIVENESS OF SIWAK (SALVADORA PERSICA) EXTRACT’S KILLING CAPABILITY AGAINST STREPTOCOCCUS VIRIDANS (IN VITRO) - Megya Agustina Dentisari; Rochman Mujayanto; Andina Rizkia Putri Kusuma (Jurnal Medali, 2022)
Background: Streptococcus viridans is an anaerobic bacteria that cause root canal infection. The irrigation materials that have antibacterial and non-toxic effects greatly support the success of root canal treatment. Sodium hypochlorite must be used with extreme caution because it can irritate the periapical tissue when used at high concentrations and has a pungent odor that interferes with patient comfort. Siwak (Salvadora persica) is a plant with antibacterial components including tannins, alkaloids, and flavonoids. This study aims to determine the effectiveness of siwak (Salvadora persica) extract’s killing capability against Streptococcus viridans (in vitro).Method: This study’s method used a post-test only control group design with experimental laboratory research consisting of 5 groups, including a negative control group (DMSO), a positive control group (sodium hypochlorite), and 3 treatment groups using siwak extract with concentrations of 55%, 60%, and 65%. This study used the maceration and dilution method with 25 samples.Result: The study’s result was analyzed using the Kruskal-Wallis non-parametric statistical test with a significant result of 0.00 (p<0.05)Conclusion: It can be concluded that siwak extract has an effective killing capability against Streptococcus viridans at a concentration of 60%.